Experiences of African-American female community college presidents using a student affairs pathway: a phenomenological study - Humphrey, Marie, author; Kuk, Linda, advisor; Davies, Timothy G., committee member; Valentine, Deborah, committee member; Hughes, Blanche, committee member (Colorado State University. Libraries, 2012)
This study explored the lived experiences of African-American women who became community college presidents from a student affairs pathway. The duality of the purpose of this study was to understand the making of a community college president per the "pathway" of student affairs, while simultaneously exploring a viable alternative to the "the pipeline" to the community college presidency for African-American women seeking the community college presidency. An interpretative phenomenological paradigm involving 10 participants with in-depth interviews was the methodology. The use of Willig's (2001) qualitative method of inquiry guided the data analysis. Five structural elements emerged from the data that described their lived experiences. These elements were summarized as: (a) Personal Pillars, (b) Professional Factors, (c) Advice, (d) Challenges, and (e) the Student Affairs Pathway. The conclusions drawn from the study involved race, gender and the pathway. One conclusion from this study was that these African-American women presidents did not allow race, gender, their student affairs background or other obstacles to hinder them from achieving the presidency. The second conclusion was that they had lived experiences that demonstrated that the student affairs pathway to the community college presidency for African-American women was viable.
Keywords: African-American female; community colleges; presidents; student affairs